RBC Transfusion Practice in Pediatric Extracorporeal Membrane Oxygenation Support. Issue 6 (June 2018) - Muszynski, Jennifer A.; Reeder, Ron W.; Hall, Mark W.; Berg, Robert A.; Shanley, Thomas P.; Newth, Christopher J. L.; Pollack, Murray M.; Wessel, David; Carcillo, Joseph; Harrison, Rick; Meert, Kathleen L.; Dean, J. Michael; et al.
Abstract : Objectives: To determine RBC transfusion practice and relationships between RBC transfusion volume and mortality in infants and children treated with extracorporeal membrane oxygenation. Design: Secondary analysis of a multicenter prospective observational study. Setting: Eight pediatric institutions within the Eunice Kennedy Shriver National Institute of Child Health and Human Development's Collaborative Pediatric Critical Care Research Network. Patients: Patients age less than 19 years old treated with extracorporeal membrane oxygenation at a participating center. Interventions: None. Measurements and Main Results: Clinical data and target hemoglobin or hematocrit values (if set) were recorded daily by trained bedside extracorporeal membrane oxygenation specialists and research coordinators. Laboratory values, including hemoglobin and hematocrit, were recorded daily using the value obtained closest to 8:00 AM. RBC transfusion was recorded as total daily volume in mL/kg. Multivariable logistic regression was used to determine the relationship between RBC transfusion volume and hospital mortality, accounting for potential confounders. Average goal hematocrits varied across the cohort with a range of 27.5–41.3%. Overall, actual average daily hematocrit was 36.8%, and average RBC transfusion volume was 29.4 mL/kg/d (17.4–49.7 mL/kg/d) on extracorporeal membrane oxygenation. On multivariable analysis, each additional 10 mL/kg/d of RBC transfusion volume was independently associated with a 9% increase in odds of hospital mortality (adjusted odds ratio, 1.09 [1.02–1.16]; p = 0.009). Conclusions: In this multicenter cohort of pediatric extracorporeal membrane oxygenation patients, daily hematocrit levels were maintained at normal or near-normal values and RBC transfusion burden was high. RBC transfusion volume was independently associated with odds of mortality. Future clinical studies to identify optimum RBC transfusion thresholds for pediatric extracorporeal membrane oxygenation are urgently needed. Abstract : Supplemental Digital Content is available in the text.